2020
DOI: 10.1111/os.12839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Percutaneous Transforaminal Endoscopic Discectomy in the Treatment of Lumbar Disc Herniation: A Retrospective Study

Abstract: The objective of the present study was to evaluate the safety and efficacy of percutaneous transforaminal endoscopic discectomy (PTED) and open fenestration discectomy (OFD) in the treatment of lumbar disc herniation (LDH). Methods: Patients in our hospital with LDH who received PTED (n = 71) and OFD (n = 39) from 2013 to 2014 were retrospectively studied. Patient information, including age, gender, visual analogue scale (VAS) score for low back pain and leg pain, body weight, height, Oswestry disability index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…25 It has received many promising reports in the treatment of degenerative diseases of the lumbar spine. 26,27 In this study, we found that PTED surgery significantly improved leg pain in patients with MC I. However, part of the back pain still remains.…”
Section: Discussionmentioning
confidence: 58%
“…25 It has received many promising reports in the treatment of degenerative diseases of the lumbar spine. 26,27 In this study, we found that PTED surgery significantly improved leg pain in patients with MC I. However, part of the back pain still remains.…”
Section: Discussionmentioning
confidence: 58%
“…In our study, flattening of the sagittal lumbar curvature happened in seven cases (43.75%). Other studies also demonstrated that flattened spines are often associated with degeneration of multiple discs and back muscle weakness, which further significantly decreases spinal flexibility and stability [25][26][27] . The relationship between sagittal morphology of the spine and intervertebral disc degeneration in adolescents will discussed in another study we did.…”
Section: Possible Pathogenesismentioning
confidence: 99%
“… 3 In recent years, with the rapid development of minimally-invasive spine surgery, percutaneous translaminar endoscopic discectomy (PTED) has provided a less invasive technique to address LDH. 4 It has become an increasingly popular surgical procedure for the treatment of LDH due to its advantages of low invasiveness, high accuracy and quick recovery. 4 , 5 However, there are some differences in the surgical approaches for different types of LDH, which poses certain difficulties for spine surgeons.…”
Section: Introductionmentioning
confidence: 99%
“… 4 It has become an increasingly popular surgical procedure for the treatment of LDH due to its advantages of low invasiveness, high accuracy and quick recovery. 4 , 5 However, there are some differences in the surgical approaches for different types of LDH, which poses certain difficulties for spine surgeons. A steep learning curve and lack of experience can often lead to serious complications, including infections, late recurrence, nerve root damage, hypoesthesia, dural tear, vascular damage and death.…”
Section: Introductionmentioning
confidence: 99%